Desenvolvimento de um conversor CC-CC de 500 W com saída variável até 300 V - Westphal, Boris Hugo (2015)
This work is directed to the study and development of a 500 W DC-DC converter, with output range up to 300 V. It is presented an analysis about the DC-DC converters, in addition of method of the switch known as pulse-width modulation (PWM). From the transformer design, became possible to determine the size of the ferrite core, define the electrical conductors, the number of turns of the windings, the switches, diodes and the output filter. The purpose of this project is to enable its use in diverse applications, aiming to serve as the local energy supply with regulated power. In future research the source developed would be used to simulate photovoltaic panels or wind energy generators. Lastly will be available for the course of electronic engineering at Universidade Tecnológica Federal do Paraná – UTFPR campus Campo Mourão.